HUBUNGAN DUKUNGAN KELUARGA DAN SIKAP IBU DENGAN PELAKSANAAN PERAWATAN METODE KANGURU PADA BAYI BERAT LAHIR RENDAH DI RUANG PERINATOLOGI RSUD H. ABDUL MANAP KOTA JAMBI TAHUN 2016 - Lidya Lidya (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The prevalence of low birth weight babies have estimated 15% of the entire world with the presence of limitations 3.3%-38%. BBLR has experiences great potential to health problems as a result of incomplete maturation and function of organs and body, RSUD H. Abdul Manap have two hundred thirty babies. There are fifty five (55) babies have born with low birth weight. 3 million infant deaths with lower weight (LBW) can be prevented with the use of appropriate interventions to the treatment to wards kangaroos. This research is quantitative research to determine the relationship of family support and attitude to the implementation of kangoroo method for low birth weight babies in perinatology at a public hospital of H. Abdul Manap Jambi 2016. The samples were 55 people by using a total of sampling. Data was collected using a questionnaire that was distributed door to door univariate and bivariate analysis with chi square test. The results of research, there are women who had a baby of low birth weight. There are 39 people (70,0%) don’t care kangaroo method. Some people didn’t get the support of family, it’s about 33 person (60%) and she think negative about that 31 people (56,4%). It’s hoped, the health workers in order to improve the health promotion of the implementation of the treatment of kangaroos in particular the impact of not making profit performance treatment method kangaroo.Keywords: Implementation of kangaroo care method, support of family, attitude